"The minde is matter moved": Nehemiah Grew on Margaret Cavendish. Issue 4 (2nd October 2017) - Begley, Justin
ABSTRACT: This essay explores an unstudied compendium to Margaret Cavendish's 1655 Philosophical and Physical Opinions that was composed by the learned physician, plant anatomist, and secretary of the Royal Society, Nehemiah Grew. Despite the growing body of scholarship on Cavendish, minimal attention has been dedicated to her early reception. But studying this compendium provides some fascinating insights into how one of the foremost thinkers of her day read, emended, and manipulated her ideas. I propose that Grew turned to Cavendish's work when developing his substance theory in the years leading up to the publication of his 1682 The Anatomy of Plants, but that shifting intellectual tides led him to critique her version of material vitalism in his 1701 Cosmologia Sacra . Supported by a transcription of the compendium as an appendix, this article also sheds light on the role that early modern pedagogical techniques and memory tools played in shaping concepts of matter and mind.